Proceeding Book The 1st International Conference of Indonesian Physioterapy Association - Ikatan Fisioterapi Indonesia (Ikatan Fisioteapi Indonesia, 2018)
ABSTRAC Proceeding Book The 1st International Conference of Indonesian Physioterapy Association